The Dynamics Of Collaboration In Addressing Stunting: An Analysis Of Stakeholder Roles In Sidenreng Rappang District - Ramlan, Pratiwi; Sukri, Phil; Abdullah, Muh. Tang; Akmal Ibrahim, Muhammad (Universitas Tribhuwana Tunggadewi, 2025)
Stunting is a complex public health problem that has a long-term impact on the quality of human resources. Despite the existence of various national regulations such as Presidential Regulation No. 72 of 2021, the reduction of stunting rates in several regions, including Sidenreng Rappang District, is still slow. This study aims to analyze the dynamics of collaboration between stakeholders in handling stunting in Sidenreng Rappang District, with a focus on principled engagement, shared motivation, and joint capacity. A qualitative approach with a case study method was used to explore the context of cross-sector collaboration, with data collected through in-depth interviews, documentation studies and participatory observation. Data analysis was conducted thematically using NVivo 12 software to categorize codes and themes. The results showed that the formal structure of collaboration had been established through the formation of the Stunting Reduction Acceleration Team (TPPS), but the internal dynamics had not developed optimally. Sectoral egos, capacity imbalances between DPOs, and low participation of the private sector and the community are the main obstacles. In addition, the lack of data integration across sectors and the dominance of top-down coordination also hinder the effectiveness of collaboration. Nevertheless, there are driving factors such as the leadership of Bappeda and the active role of PKK cadres that can be optimized. This research makes a theoretical contribution to the development of locally-based collaborative governance models and offers practical recommendations, such as the establishment of a community communication forum, activation of local CSR, cross-sector training, and development of a shared data system. The implication of this research confirms that the success of handling stunting is not only determined by the policy structure, but also depends heavily on the quality of the collaboration dynamics between actors at the local level.Stunting merupakan masalah kesehatan masyarakat yang kompleks dan berdampak jangka panjang terhadap kualitas sumber daya manusia. Meskipun telah terdapat berbagai regulasi nasional seperti Peraturan Presiden Nomor 72 Tahun 2021, penurunan angka stunting di beberapa daerah, termasuk Kabupaten Sidenreng Rappang, masih berjalan lambat. Penelitian ini bertujuan untuk menganalisis dinamika kolaborasi antar pemangku kepentingan dalam penanganan stunting di Kabupaten Sidenreng Rappang, dengan fokus pada keterlibatan yang terarah (principled engagement), motivasi bersama (shared motivation), dan kapasitas kolektif (joint capacity). Pendekatan kualitatif dengan metode studi kasus digunakan untuk mengeksplorasi konteks kolaborasi lintas sektor, dengan pengumpulan data melalui wawancara mendalam, studi dokumentasi, dan observasi partisipatif. Analisis data dilakukan secara tematik menggunakan bantuan perangkat lunak NVivo 12 untuk mengelompokkan kode dan tema. Hasil penelitian menunjukkan bahwa struktur formal kolaborasi telah terbentuk melalui pembentukan Tim Percepatan Penurunan Stunting (TPPS), namun dinamika internal belum berkembang secara optimal. Ego sektoral, ketidakseimbangan kapasitas antar OPD, dan rendahnya partisipasi sektor swasta serta masyarakat menjadi hambatan utama. Selain itu, kurangnya integrasi data lintas sektor dan dominasi koordinasi top-down turut menghambat efektivitas kolaborasi. Meskipun demikian, terdapat faktor pendorong seperti kepemimpinan Bappeda dan peran aktif kader PKK yang dapat dioptimalkan. Penelitian ini memberikan kontribusi teoretis terhadap pengembangan model collaborative governance berbasis lokal serta menawarkan rekomendasi praktis, seperti pembentukan forum komunikasi komunitas, aktivasi CSR lokal, pelatihan lintas sektor, dan pengembangan sistem data bersama. Implikasi dari penelitian ini menegaskan bahwa keberhasilan penanganan stunting tidak hanya ditentukan oleh struktur kebijakan, tetapi juga sangat bergantung pada kualitas dinamika kolaborasi antar aktor di tingkat lokal.